2022
DOI: 10.1371/journal.pone.0266814
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lp(a) and course of COVID-19: Is there a relationship?

Abstract: Background Lipoprotein (a)–Lp(a) has proinflammatory, prothrombotic and proatherogenic properties and may theoretically influence the course of COVID-19. Objectives The aim of the study was to explore whether patients hospitalized due to COVID-19 with Lp(a) ≥30mg/dl may develop a worse course of the disease, increased incidence of thromboembolic complications, intubation and ICU hospitalization or death. Patients and methods A retrospective analysis was performed of 124 patients hospitalized due to COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Our observation of a non-significant association between D-dimer and Lp(a) levels is in contrast with the results of two previous studies [26,29]. Indeed, Kaltoft et al previously reported that two-fold higher D-dimer levels were associated with 14% higher Lp(a) levels among 211 patients admitted with COVID-19 [29].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our observation of a non-significant association between D-dimer and Lp(a) levels is in contrast with the results of two previous studies [26,29]. Indeed, Kaltoft et al previously reported that two-fold higher D-dimer levels were associated with 14% higher Lp(a) levels among 211 patients admitted with COVID-19 [29].…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of an association between Lp(a) and venous thrombotic events observed in our study fits into the context of inconsistent literature data. Pawlos et al reported comparable rates of pulmonary embolism between COVID-19 patients with Lp(a) < 30 mg/dL and those with Lp(a) ≥ 30 mg/dL [26]. In contrast, Nurmohamed et al showed a three-fold higher risk of venous thromboembolism with increasing Lp(a) levels during the hospital stay [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note are also the observations that Lp(a) is involved in thrombotic complications of COVID-19 patients [13 ▪ ,14 ▪ ,15].…”
Section: Burning Questions To Be Addressedmentioning
confidence: 98%
“…In general, the effect of expression quantitative trait loci (eQTL) is cell-type specific and context-dependent. Previous reports and data from the ImmuNexUT immune cell gene expression database (https://www.immunexut.org) have shown that the risk allele of rs2297550 has a negative eQTL effect on the IKBKE gene in T and B cells, whereas it is associated with higher IKBKE expression in nonstimulated monocytes (3,4). Furthermore, the eQTL effect might be different in individuals with SLE than in healthy controls (5).…”
mentioning
confidence: 99%